Strategies for Managing the Structural and Dynamic Consequences of Project Complexity - Serghei Floricel; Sorin Piperca; Richard Tee (Complexity)
We propose a theoretical framework that highlights the most important consequences of complexity for the form and evolution of projects and use it to develop a typology of project complexity. This framework also enables us to deepen the understanding of how knowledge production and flexibility strategies enable project participants to address complexity. Based on this understanding, we advance a number of propositions regarding the strategies that can be most effective for different categories of complexity. These results contribute to the integration of various strands in the research on project complexity and provide a roadmap for further research on the strategies for addressing it.